Винни-Пух: повесть-сказка / А. А. Милн, Б. В. Заходер ; худож. Э. В. Назаров - Милн Алан Александр (Самовар, 1998)
Экземпляры: (20220121) / Инвентарный номер: / Цена: / Сис.шифр: 84(4/8) / Авт.знак: М 60 / ББК: 84(4Вел)